2023
DOI: 10.3390/ijms24109050
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Induced by Cadmium and Diabetes: A Quantitative Case-Control Study

Abstract: Kidney disease associated with chronic cadmium (Cd) exposure is primarily due to proximal tubule cell damage. This results in a sustained decline in glomerular filtration rate (GFR) and tubular proteinuria. Similarly, diabetic kidney disease (DKD) is marked by albuminuria and a declining GFR and both may eventually lead to kidney failure. The progression to kidney disease in diabetics exposed to Cd has rarely been reported. Herein, we assessed Cd exposure and the severity of tubular proteinuria and albuminuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The participants of the MR study selected from the GWAS data of the European population are the older adult ( 37 ), while the cross-sectional study involves the general population, and the overall blood Cd level is significantly lower than that of the older adult. Some studies suggest that Cd exposure may promote the progression of DKD in diabetic patients ( 63 , 64 ). Overall, our MR research results support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The participants of the MR study selected from the GWAS data of the European population are the older adult ( 37 ), while the cross-sectional study involves the general population, and the overall blood Cd level is significantly lower than that of the older adult. Some studies suggest that Cd exposure may promote the progression of DKD in diabetic patients ( 63 , 64 ). Overall, our MR research results support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Cd-associated GFR reductions, albuminuria, and hypertension were more severe in those who had diabetes [ 129 , 145 , 149 , 150 , 151 ]. These results are replicated in experimental studies [ 152 , 153 ].…”
Section: Cadmium the Liver Kidney And Diabetes Typementioning
confidence: 99%
“…Kornhauser et al reported that plasma Se was negatively associated with the severity of diabetic nephropathy in patients with type 2 diabetes 9 . There exists scientific evidence indicating that low levels of Cd exposure exacerbate the progression of kidney disease in diabetics 10 . However, the relationship between these heavy metals and diabetic retinopathy is poorly studied.…”
Section: Introductionmentioning
confidence: 99%